A Highly Sensitive Three Axis Piezoelectric Microaccelerometer for High Bandwidth Applications - Tahmasebipour, Mohammad; Vafaie, Ali (Micro and Nanosystems, 2017)
Background: MEMS piezoelectric accelerometers are used in many different applications. In Some applications, accelerometers have to measure the acceleration at high frequency ranges. Objective: Due to the inverse relation between their sensitivity and bandwidth, high-bandwidth accelerometers generally have low sensitivity. By increasing their sensitivity, these accelerometers can measure vibrations with low amplitudes in a wide frequency range. Method: In this study, a single axis piezoelectric accelerometer with sensitivity higher than conventional accelerometers is introduced for high-bandwidth applications. The behavior of this micro-accelerometer including its resonance mode shapes, proof mass displacement amplitude, and output characteristics, as well as its stress distribution, polarity, and the electric potential generated in the piezoelectric layer are also studied by the finite element method. In addition, an idea to have a three axis accelerometer with higher sensitivity is proposed. Results: The proposed single axis accelerometer has 0.54 mV/g sensitivity and 10 kHz bandwidth. The three axis accelerometer has 7e-3 mV/g sensitivity for acceleration in x-y plane with the same bandwidth. Conclusion: This study proposed a piezoelectric accelerometer (based on a membrane attached to a proof mass) for high bandwidth applications with a sensitivity double that of its similar counterparts. To evaluate the performance of the proposed model, its characteristics were compared with those of a piezoelectric accelerometer with a circular membrane cross section. Although both studied structures had identical spring stiffness and proof mass, we observed that the maximum stress developed in the membrane for the proposed model is more than the circular accelerometer under a same acceleration. Therefore, the electric potential generated via the piezoelectric layer was greater in the square accelerometer.
Keywords: three axis accelerometer